Drying Kinetics and Chemical Properties of Mango. (11th August 2022) - Ampah, Jonathan; Dzisi, Komla Agbeko; Addo, Ahmad; Bart-Plange, Ato
Abstract : Four mango fruit varieties of average slice thickness 0.6 cm and slice area 10 cm 2 were dried using a mechanical dryer at varied temperatures, 55°C, 65°C, and 75°C. In general, the moisture content (MC) for all samples analyzed decreased with increasing drying time. Palmer and Haden varieties recorded the lowest MCs of 8.7% (w.b.) and 9.3% (w.b.), respectively, when dried for 14 h at 65°C. Palmer variety with the highest initial MC of 87.2% (w.b.) recorded a low final MC of 8.7% (w.b.) when dried for 14 h at 55°C. Moisture ratio decreased from 1.00 to 0.13, 1.00 to 0.12, 1.00 to 0.12, and 1.00 to 0.10 at 55°C for Kent, Keitt, Haden, and Palmer varieties, respectively. Kent, Keitt, Haden, and Palmer varieties recorded effective moisture diffusivity values of 5.90 × 10 – 7, 6.40 × 10 − 7, 6.57 × 10 − 7, and 7.33 × 10 − 7 m 2 / s, respectively. Vitamin C content of 158.34 mg/100 g recorded for Palmer was highest compared to the other varieties. Activation energy values of samples analyzed were between 19.90 and 25.50 kJ/mol for the drying temperature range. The activation energy recorded by Haden variety was highest compared to the rest. Also, twelve mathematical models were analyzed in predicting the moisture ratio of mango fruit slices during thin layer drying. The results showed that the Midilli, Page, Wang and Singh, and Logarithmic models exhibited supremacy in predicting drying behavior compared to the other eight models.